The association of serum 25-hydroxyvitamin D and Alzheimer’s Disease: a meta-analysis - Siti Sarahdeaz Fazzaura Putri; Irfannuddin Irfannuddin; Krisna Murti; Yudianita Kesuma; Noriyuki Koibuchi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Serum 25-hydroxyvitamin D deficiency has been suggested as a promising prognostic factor for dementia. Meta-analysis published revealed statistically significant differences of 25-hydroxyvitamin D levels in patients with Alzheimer's disease (AD) but other studies have been published since then.The purpose of present study was to quantify the association of serum 25-hydroxyvitamin D and AD. Literature search was performed from inception up to November 22 using Pubmed database. Based on the pooled analysis, patients with Alzheimer’s disease tend to have a vitamin D deficiency relative to patients with normal cognitive function. These results strongly support the involvement of vitamin D as a critical disease-modifying variable in the reduction of AD symptoms.